Routes of Passage: Rethinking the African Diaspora. (Ruth Simms Hamilton African Diaspora Ser., 2006)
Routes of Passage provides a conceptual, substantive, and empirical orientation to the study of African people worldwide. The book addresses issues of geographical mobility and geosocial displacement; changing culture, political, and economic relationships between Africa and its diaspora; interdiaspora relations; political and economic agency and social mobilization, including cultural production and psychocultural transformation; existence in hostile and oppressive political and territorial space; and confronting interconnected relations of social inequality, especially class, gender, nationality, and race.